A Systematic Literature Review on the Influence of Road Curves on Urban Mobility Performance and Safety - Habibi, Royhan Farhan; Prasetyo, Cepy; Ivan, M. Taufik; Rijaluddin, Arief; Prasetijo, Joewono (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The geometric design of road bends is an important factor affecting smooth mobility and traffic safety in urban areas. This study aims to systematically evaluate how elements such as bend radius, superelevation and sight distance affect traffic performance and crash risk. The Systematic Literature Review (SLR) method was used with reference to the PRISMA protocol, analyzing 970 scientific publications from 2000 to 2025 obtained through Google Scholar using Publish or Perish. Bibliometric data were analyzed and visualized with VOSviewer to identify research trends, keyword linkages, and author collaboration patterns. The results showed five main clusters, namely horizontal design, user safety, driver behavior, traffic efficiency, and socio-environmental impacts. It was found that sub-optimal corner design significantly increases crash potential, especially in sharply curved areas with low visibility and heavy traffic. The study also showed the dominance of contributions from developed countries, while developing countries are still limited despite facing the challenges of greater urbanization and complex infrastructure. Therefore, a multidisciplinary and contextual approach is needed in planning curve designs that are responsive to local conditions. This study emphasizes the importance of utilizing bibliometric technology for the design of bend designs. Therefore, a multidisciplinary and contextual approach is needed in planning bend designs that are responsive to local conditions. This study emphasizes the importance of utilizing bibliometric technology to support data-driven decision-making, strengthen the integration of technical, social, and environmental aspects, and design adaptive and sustainable urban transport.